Sedative effects of inhaled essential oil components of traditional fragrance Pogostemon cablin leaves and their structure–activity relationships - Ken Ito; Yasuko Akahoshi; Michiho Ito; Shuji Kaneko (Journal of Traditional and Complementary Medicine, 2016)
Plants rich in essential oils, such as Pogostemon cablin (P. cablin; 廣藿香 guǎng huò xiāng), have been used for aromas and as herbal medicines since ancient times because of their sedative effects. We investigated the sedative effects of hexane extract from P. cablin using locomotor activity in mice. Inhalation of P. cablin hexane extract exhibited significant sedative activity in a dose-dependent manner. In order to isolate the active constituents, the extract was fractionated and diacetone alcohol was identified as an active compound. Inhalation of diacetone alcohol significantly reduced murine locomotor activity in a dose-dependent manner, and this effect was not observed in olfaction-impaired mice. We examined the structure–activity relationship of diacetone alcohol and similar compounds. The ketone group at the two-position and number of carbons may play important roles in the sedative activity of diacetone alcohol.